Evidence for an elongated Achilles tendon in Australopithecus. Issue 9 (13th March 2020) - McNutt, Ellison J.; DeSilva, Jeremy M.
Abstract: Modern humans have the longest Achilles tendon (AT) of all the living primates. It has been proposed that this anatomy increases locomotor efficiency and that its elongation may have played a crucial role in the origin and early evolution of the genus Homo . Unfortunately, determining the length of the AT in extinct hominins has been difficult as tendons do not fossilize. Several methods have been proposed for estimating the length of the AT from calcaneal morphology, but the results have been inconclusive. This study tested the relationship between the area of the superior calcaneal facet and AT length in extant primates. The superior facet is instructive because it anchors the retrocalcaneal bursa, a soft tissue structure which helps to reduce friction between the AT and the calcaneus. Calcanei from 145 extant anthropoid primates from 12 genera were photographed in posterior view and the relative superior facet size quantified. AT lengths were obtained from published sources. The relative area of the superior facet is predictive of AT length in primates ( R 2 = 0.83; p  < .001) and differs significantly between the great apes and humans ( p  < 0.001). When applied to fossil Australopithecus calcanei, our results suggest that australopiths possessed a longer, more human‐like, AT than previously thought. These findings have important implications for the locomotor capabilities of Australopithecus, including their capacity for endurance running and climbing.